Microprocessor protection relays: new prospects or new problems? - Gurevich, Vladimir (НТУ "ХПИ", 2006)
The internal architecture and principles of operation of microprocessor-based devices including so-called "microprocessor protective relays" have little in common with devices called "electric relays". But microprocessor-based relay protection devices are gradually driving out the traditional electromechanical and even electronic relay protection of virtually from all fields of power and electrical engineering. Advantages of microprocessor-based protection means over traditional ones are far from being absolute or obvious, yet this is a general trend. In reality, however, microprocessorbased protection means have several specific 12 drawbacks too. In this paper, some of these problems are discussed
Keywords: microprocessor-based relay; protection device; advantages; drawbacks